2021
DOI: 10.1016/j.imlet.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike protein enhances ACE2 expression via facilitating Interferon effects in bronchial epithelium

Abstract: Objective In this study, we focused on the interaction between SARS-CoV-2 and host Type I Interferon (IFN) response, so as to identify whether IFN effects could be influenced by the products of SARS-CoV-2. Methods All the structural and non-structural proteins of SARS-CoV-2 were transfected and overexpressed in the bronchial epithelial cell line BEAS-2B respectively, and typical antiviral IFN-stimulated gene (ISG) ISG15 expression was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…As S-protein assists in the ACE2-receptor-mediated internalization of SARS-CoV-2, the host IFN responses could, thus, stimulate the capability of the virus to preserve cellular targets expression in neighboring epithelial cells ( Ziegler et al, 2020 ). Remarkably, screening of non-structural proteins plus structural proteins of SARS-CoV-2 supports the S-protein to facilitate the IFN-α effector, which further encourages the IFN-stimulated genes (ISGs) signaling and radically enhanced the production of long ACE2 protein in the bronchial epithelial cell line BEAS-2B ( Zhou et al, 2021 ), as depicted in Fig. 2 .…”
Section: Role Of Ace2 In Sars-cov-2 Infectionmentioning
confidence: 90%
See 2 more Smart Citations
“…As S-protein assists in the ACE2-receptor-mediated internalization of SARS-CoV-2, the host IFN responses could, thus, stimulate the capability of the virus to preserve cellular targets expression in neighboring epithelial cells ( Ziegler et al, 2020 ). Remarkably, screening of non-structural proteins plus structural proteins of SARS-CoV-2 supports the S-protein to facilitate the IFN-α effector, which further encourages the IFN-stimulated genes (ISGs) signaling and radically enhanced the production of long ACE2 protein in the bronchial epithelial cell line BEAS-2B ( Zhou et al, 2021 ), as depicted in Fig. 2 .…”
Section: Role Of Ace2 In Sars-cov-2 Infectionmentioning
confidence: 90%
“…2 . Mechanistically, upregulation of long ACE2 protein was demonstrated with higher phosphorylation of signal transducer and activator of transcription 1 (STAT1) and STAT2 as a result of reinforcing their signaling with upstream Janus kinase, i.e., JAK1, by S-protein of SARS-CoV-2 to aid viral access in the bronchial epithelium ( Zhou et al, 2021 ). Likewise, IFN-γ was noted to promote cellular differentiation into enterocytes expressing ACE2, supporting the high viral infection and replication ( Heuberger et al, 2021 ).…”
Section: Role Of Ace2 In Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Lei et al [57], for example, demonstrated that the spike protein down-regulated ACE2 in Syrian hamster vascular endothelial cells, which led to inhibited mitochondrial function and cell damage. In a later in vitro study, however, the spike protein was shown to upregulate bronchial epithelial cell ACE2 expression via activation of the Type I IFN signaling pathway [58]. These two studies indicate that the effect of this spike protein on ACE2 expression is tissue or species-specific.…”
Section: Bioactivity Of the Sars-cov-2 Spike Proteinmentioning
confidence: 91%
“…Interestingly, ACE2 is also itself an ISG, and its expression is significantly induced by multiple IFN types, particularly β (I) and γ (II) [ 134 , 138 ]. Although one would assume this to be detrimental in the setting of SARS-CoV-2 infection (even the S protein itself has been shown to induce ACE2 expression) [ 139 ], in vitro studies have not shown that IFN induced ACE2 to enhance the virus’s replication, perhaps due to the other cellular defenses activated by the interferon response [ 138 ]. One study, however, showed that it was not the full ACE2 protein whose expression was induced by interferons, but rather a truncated isoform that did not possess the carboxylase function of ACE2 nor bind to SARS-CoV-2, and its exact function remains unknown [ 140 , 141 ].…”
Section: Interferon-stimulated Genesmentioning
confidence: 99%